The Investment Behavior through Supply Chain Strategy of Acehness Entrepreneurs, Indonesia - Jumadil Saputra; Iswadi Iswadi; Yunina Yunina; Muhammad Haykal; Wahyuddin Albra (International Journal of Supply Chain Management, 2019)
The aim of this is to analyze the investment behavior of Acehnese entrepreneurs by considering the individual characteristics of entrepreneurs. This study was analyzed using a quantitative descriptive approach. The number of samples was 150 Aceh Entrepreneurs in 10 districts/cities in Aceh. The selected entrepreneurs who have been designated as Taxable Entrepreneurs (PKP) by the Directorate General of Taxes. The sampling technique used is judgment sampling. The research data collected by using a closed questionnaire. The results of the study show that Acehnese entrepreneurs have risk-averse behavior in making investment decisions. The results of the study also show that Acehnese entrepreneurs consider investments by sharia principles. Entrepreneurs with an older age tend to have alternative investments in financial assets. Factors of saturation and reliability cause this tendency. Older entrepreneurs are becoming increasingly uncomfortable with the business they are running right now, but they are worried about the significant risks of diversifying investment into financial assets. Education needs to be given about investing in the financial sector for Acehnese entrepreneurs, especially for older entrepreneurs.